Facile microwave synthesis of Zinc Ferrite@NCDs for photocatalytic degradation of fluoroquinolone antibiotics - Kaushal, Neha; Sarraf, Sonu; Basu, Aviru Kumar; Mishra, Sunita; Saha, Avishek (Materials Chemistry and Physics, 2024)
Zinc ferrite (ZnFe2O4) composites have attracted growing interest in photocatalytic water purification. Herein, the hybrids of zinc ferrite and nitrogen-doped carbon dots (ZnF@x%NCDs) were synthesized via facile micro-wave synthesis. X-ray diffraction and Raman characterization confirm the formation of the spinel structure, and elemental composition has been analyzed by X-ray photoelectron spectroscopy. The photocatalytic activity of ZnF@x%NCDs was evaluated via the decomposition of ciprofloxacin and norfloxacin under visible light illumination. We noted that 20 % weight loading of NCDs led to the highest (similar to 79.2 %) ciprofloxacin (CIP) degradation. Diffuse reflectance measurements demonstrate the reduction of the band gap in composites ZnF@20%NCDs (1.91 eV) compared with bare ZnF (2.03 eV); moreover, the hybridization of zinc ferrites with NCDs results in enhanced photocurrent density and surface area. The effect of experimental parameters, including the role of photocatalyst dosage, pH value, and initial concentration of pollutants on the degradation of CIP, have also been investigated.
Keywords: Carbon dots; Ciprofloxacin degradation; Norfloxacin degradation; Photocatalysis; Zinc Ferrite

Novel GO hoisted SnO2-BiOBr bifunctional catalyst for the remediation of organic dyes under illumination by visible light and electrocatalytic water splitting - Dhillon, Manshu; Naskar, Abhishek; Kaushal, Neha; Bhansali, Shekhar; Saha, Avishek; Basu, Aviru Kumar (NANOSCALE, 2024)
Keywords: Chemistry; Multidisciplinary; Nanoscience & Nanotechnology

Oxidase-like nanozyme activity of ultrathin copper metal–organic framework nanosheets with high specificity for catechol oxidation - Singh, Ajit Kumar; Sharma, Deepika; Singh, Devesh Kumar; Sarraf, Sonu; Basu, Aviru Kumar; Ganesan, Vellaichamy; Saha, Avishek (ChemCatChem, 2025)
In nature, catechol oxidase catalyzes the oxidation of o-diphenol to o-quinone to produce a series of highly important polyphenolic natural products. Although mimicking the functionality of natural enzyme using a nanozyme was found to be beneficial, attaining a high specificity is challenging. Herein, we have explored the thickness-dependent oxidase activity and specificity of Cu-metal-organic framework (MOF) nanosheets. The unique synthetic method offers control over the thickness of the Cu-MOF nanosheets. The ultrathin (4 nm) Cu-MOF (Cu-UMOF) nanosheets as an oxidase nanozyme exhibit high specificity for catechol oxidation without having any peroxidase activity. Interestingly, the thicker (20–30 nm) Cu-MOF nanosheets showed poor catechol oxidase and peroxidase activity. The binuclear Cu-center, coordinative, and electronic unsaturation tuned electronic structure in Cu-UMOF, resulting in higher specificity for catechol oxidation than thicker Cu-MOF.